The Digital Twin in Medicine: A Key to the Future of Healthcare? - Sun, Tianze; He, Xiwang; Song, Xueguan; Shu, Liming; Li, Zhonghai (Frontiers in Medicine, 2022)
There is a growing need for precise diagnosis and personalized treatment of disease in recent years. Providing treatment tailored to each patient and maximizing the efficacy and efficiency are broad goals of healthcare system. As an engineering concept that connects the physical entity and digital space, digital twin (DT) entered our lives at the beginning of Industry 4.0. It is evaluated as a revolution in many industrial fields and has shown the potential to be widely used in the field of medicine. This technology can offer innovative solutions for precise diagnosis and personalized treatment processes. Although there are difficulties in data collection, data fusion and accurate simulation at this stage, we speculated that DT may have an increasingly use in the future and will become a new platform for personal health management and healthcare services. We introduced the DT technology and discussed the advantages and limitations of its applications in medical field. The aim of this paper is to provide a prospective that combining big data, Internet of Things (IoT), and artificial intelligence (AI) technology, DT will help establish high-resolution models of patients to achieve precise diagnosis and personalized treatment.